TADBIR URUS SYARIAH BAGI PENYELESAIAN ISU-ISU PEMBANGUNAN WAKAF DI MALAYSIA: KAJIAN KES DI BEBERAPA NEGERI TERPILIH: Shariah Governance on Resolutions of Waqf Development Issues in Malaysia: Case Studies in Selected States - Ibrahim, ‘Adnin; Ab Rahman, Asmak (Jurnal Syariah, 2024)
This paper analyzes the governance implemented to resolve Shariah-related issues in the development of waqf in Malaysia. The study adopts a qualitative research approach employing a collective case study design. Four states were selected as study samples, and semi-structured interviews were conducted with officers from the State Islamic Religious Council (SIRC) or its subsidiaries appointed as mutawalli, officers from the State Mufti Department, as well as Muftis, Deputy Muftis, or members of the State Fatwa Committee. Thematic analysis is employed to highlight themes related to the governance of resolving Shariah issues in the development of waqf in Malaysia. The findings indicate that the development of waqf in Malaysia is subject to governance at the state rather than federal level. Consequently, in the context of Shariah governance for waqf development, two institutions in each state are involved, namely the waqf institution as mutawalli managing waqf assets and the Fatwa Committee. Additionally, the Fatwa Committee plays an advisory role for the waqf institution in ensuring Shariah compliance of products and waqf development management.